The Effect Of The Rebozzo Technique On The Progress Of The Active Phase Of First Stage Labor In The Clinic Pratama Citra Marindal Deli Old Deli Serdang Regency Year 2025 - Eka Sriwahyuni; G.F. Gustina Siregar; Fitri Rahmadan Nasution (Universitas Prima Indonesia, 2026)
Optimal labor progress during the first stage's active phase is a crucial factor in the smoothness of the normal labor process. Among the non-pharmaceutical methods that can support the acceleration of cervical dilation is the Rebozzo technique, a traditional Mexican technique that aims to relax the pelvic muscles and improve the position of the fetus. Goal To ascertain how the Rebozzo approach affects the development of active phase I labor. Method: The research employed a two-group posttest-only design methodology and a quasi-experiment design. Thirty mothers who were giving birth during the first stage's active period made up the sample. divided into two groups: intervention (given the Rebozzo technique) and control (without intervention). The total sampling technique was used, and measurements were taken based on the duration of the first stage and cervical dilation. Data analysis used the Paired Sample t-Test. Results: A p-value of 0.000 (<0.05) was obtained, indicating that the Rebozzo technique had a significant effect on accelerating the progress of active phase I labor. Conclusion: The Rebozzo technique is efficient as a non-pharmacological technique to aid in the work process throughout the first stage's active phase.